A review of the development of Polymerase Chain Reaction technique and its uses in Scientific field - Lucyenne Angeline Giri Putra; Christianus Jodi Yonathan; Nabila Imania Niedhatrata; Mochammad Hilmy Rizka Firdaus; Jessica Renata Yoewono (Stannum : Jurnal Sains dan Terapan Kimia, 2020)
PCR (Polymerase Chain Reaction) is a scientific term and technique in molecular biology which able to generate copies of a specific DNA from two short oligodeoxynucleotide sequences (also called primers) by a polymerase-dependent repetitive thermal reaction. PCR technique brought a revolution in science especially in molecular biology since its first discovery back in 1984 as its simplicity and not a time-consuming trait. Over the past decades, PCR techniques have been modified to make it suitable for the application in each scientific field. PCR nowadays is involved in almost all studies that required DNA fragments manipulation including in food and medical analysis. By taking advantage of this revolutionary technique and if developed and used well, it would become very beneficial for humanity in many aspects